SANITASI LINGKUNGAN MASYARAKAT DI DESA CITAMALU KECAMATAN SIBERUT BARAT KABUPATEN KEPULAUAN MENTAWAI - -, Renaldus - (Pendidikan Geografi, 2014)
This study aims to obtain data and information and in-depth analyzes of the toilets to the public, community waste management facilities and waste water treatment facility in the village community household Simatalu Western District of Siberut Island District Mentawai.Penelitian a qualitative study. The informants are people in the village sanitation Simatalu that the environment is not good. The technique of taking informants conducted by purposive sampling technique. Pengumplan data were interviews, observation, and documentation. The data analysis techniques with data reduction, data presentation and draw conclusions or verification. Techniques to test the validity of the data is done by increasing persistence, triangulation and discussions with colleagues.The results showed: 1) a means of public toilets in the village of West Kecamatan Siberut Simatalu Mentawai Islands is not good. 2) Means of community waste management in Siberut District West Village Simatalu Mentawai Islands is still considered not good. 3) Means of household waste water management in the village community Simatalu Kecamatan West Siberut Mentawai Islands regency is still quite bad.